2023
DOI: 10.1002/1873-3468.14635
|View full text |Cite
|
Sign up to set email alerts
|

TDP‐43 N‐terminal domain dimerisation or spatial separation by RNA binding decreases its propensity to aggregate

Abstract: Aggregation of the 43 kDa TAR DNA‐binding protein (TDP‐43) is a pathological hallmark of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). RNA binding and TDP‐43 N‐terminal domain dimerisation has been suggested to ameliorate TDP‐43 aggregation. However, the relationship between these factors and the solubility of TDP‐43 is largely unknown. Therefore, we developed new oligonucleotides that can recruit two TDP‐43 molecules and interfere with their intermolecular interactions via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…As previously reported, 32 , 55 biochemical assays showed that longer GU-oligonucleotides promoted multivalent TDP-43 binding, compared to monovalent (GU)6 ( Figure 1 ). Both native EMSA assays and BS3 cross-linking-SDS-PAGE demonstrated stronger TDP-43 RRM1,2 multimerization for 34-nt Clip34nt and 36-nt (GU)16 compared to 24-nt (‘AUG12’)2.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As previously reported, 32 , 55 biochemical assays showed that longer GU-oligonucleotides promoted multivalent TDP-43 binding, compared to monovalent (GU)6 ( Figure 1 ). Both native EMSA assays and BS3 cross-linking-SDS-PAGE demonstrated stronger TDP-43 RRM1,2 multimerization for 34-nt Clip34nt and 36-nt (GU)16 compared to 24-nt (‘AUG12’)2.…”
Section: Discussionsupporting
confidence: 83%
“…TDP-43 LLPS regulates the native size of TDP-43 nuclear RNP complexes, which in turn dictates TDP-43 nucleocytoplasmic localization. 56 Since GU-RNA modulates TDP-43 LLPS in a length- and motif-dependent manner, 33 , 55 the observed GU-oligo-induced effects on TDP-43 localization (and function, discussed later) may be influenced by changes in TDP-43 LLPS. RNA motifs containing pure GU repeats differ in their ability to promote TDP-43 phase transition compared to GU intermixed with A and C. 55 Indeed, image analysis of oligo-induced changes in nuclear TDP-43 granules, likely composed of numerous TDP-43 RNPs, showed marked differences between oligos containing pure GU-repeats ((GU)16 and (‘AUG12’)2) versus the intermixed sequence of Clip34nt ( Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, 32,55 biochemical assays showed that longer GU-oligonucleotides promoted multivalent TDP-43 binding, compared to monovalent (GU)6 (fig 1). Both native EMSA assays and BS3 crosslinking-SDS-PAGE demonstrated stronger TDP-43 RRM1,2 multimerization for 34-nt Clip34nt and 36-nt (GU)16 compared with 24-nt ('AUG12')2.…”
Section: Rna Sequence-specific Drivers Of Multivalent Tdp-43 Rnpssupporting
confidence: 80%
“…Surprisingly, oligo localization within cells did not predict the effect on TDP-43 nucleocytoplasmic localization and was inversely correlated, with ('AUG12')2 being the most nuclear and (GU)16 being equally distributed between the nucleus and cytoplasm. Future proteomic analysis could enable the identification of nuclear vs 56 Since GU-RNA modulates TDP-43 LLPS in a length-and motif-dependent manner, 33,55 the observed GU-oligo-induced effects on TDP-43 localization (and function, discussed below) may be influenced by changes in TDP-43 LLPS. RNA motifs containing pure GU repeats differ in their ability to promote TDP-43 phase transition compared to GU intermixed with A and C. 55 Indeed, image analysis of oligoinduced changes in nuclear TDP-43 granules, likely composed of numerous TDP-43 RNPs, showed marked differences between oligos containing pure GU-repeats ((GU)16 and ('AUG12')2) versus the intermixed sequence of Clip34nt (fig S1).…”
Section: Oligonucleotide-induced Regulation Of Tdp-43 Localization In...mentioning
confidence: 99%
See 1 more Smart Citation